Farmstead and artisanal cheeses: Adding value to milk at the farmers’ doorstep - Sabikhi, Latha; Bhongle, Pravin A; M.H., Sathish Kumar (Indian Journal of Dairy Science, 2015)
Indian dairy industry is diversifying its production pattern to include specialty foods meant for specific targeted populations. Today consumers tend to believe that food that is purchased directly from the farmer is produced in an agriculturally responsible manner, and is, therefore, better tasting and fresher than what they can purchase from a supermarket. Traditional and farm-produced cheeses have niche and premium markets in the western countries. On similar lines, if cheesemaking principles can be applied to make artisanal farmstead cheeses in India, it will provide an impetus to the farmer for value addition, product diversification and augmented farm income.